Head Teachers’ Characteristics and Instructional Leadership in Curriculum Implementation in Secondary Schools, Siaya County, Kenya - Okoth, Ursulla Achieng (European Scientific Journal, ESJ, 2018)
Personal or background characteristics can influence head teachers instructional leadership in schools. This study investigated the relationship, if any, between the head teacher’s instructional leadership and the head teacher’s background variables such as education/ professional qualification, gender, age,p and teaching experience in the implementation of curriculum (Environmental Education) in secondary schools. Thirty headteachers and 183 teachers randomly sampled participated. Questionnaire was used to collect data in the survey. Findings: The Instructional Leadership Mean Score for mostvariables was moderate,Instructional Leadership Mean Score was independent of head teacher characteristics such as sex, age, and teaching experience but dependent on head teacher qualification. Recommendation: Quality Assurance and Standards officers need to monitor instructions in schools regularly to assist heads,Training of headteacherson instructional leadership should be ongoing and be ensured byboth Teachers Service Commission and Kenya Education Management Institute.